2017
DOI: 10.3847/2041-8213/aa5d54
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Solar Filament Plasma Inferred from In Situ Observations of Elemental Abundances

Abstract: Solar filaments/prominences are one of the most common features in the corona, which may lead to energetic coronal mass ejections (CMEs) and flares when they erupt. Filaments are about one hundred times cooler and denser than the coronal material, and physical understanding of their material origin remains controversial. Two types of scenarios have been proposed: one argues that the filament plasma is brought into the corona from photosphere or chromosphere through a siphon or evaporation/injection process, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Yet, it is reasonable that they remain similarly cold and dense, especially when the mixing with the background plasma is not very effective. Thus, the study provides a possible mechanism for the origin of the transient cold-dense plasma that is sometimes detected in the solar wind by spacecrafts (Yao et al 2010;Lepri & Zurbuchen 2010;Song et al 2017). …”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, it is reasonable that they remain similarly cold and dense, especially when the mixing with the background plasma is not very effective. Thus, the study provides a possible mechanism for the origin of the transient cold-dense plasma that is sometimes detected in the solar wind by spacecrafts (Yao et al 2010;Lepri & Zurbuchen 2010;Song et al 2017). …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Though it is rare, the transient cold-dense plasma is sometimes detected in the solar wind with in situ observations. Most of the cases are associated with interplanetary coronal mass ejections (ICMEs) or magnetic clouds (MCs), and the cold-dense plasma is identified as the ICME core consisting of filament material that shows a low proton temperature, a high proton density, a flux rope, and the ions with low charge states (Yao et al 2010;Lepri & Zurbuchen 2010;Song et al 2017). On the other hand, for normal solar winds not associated with ICMEs/MCs, the origin of their cold-dense plasma are not resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the case no. 8 as shown in Figure a, Song et al () also found the Q <Fe> in one case decreasing from high to low level, and this could be a manifestation of cold filament material in MCs (Song et al, ). However, cases with three peaks higher than 12 (similar to case no.…”
Section: Discussionmentioning
confidence: 74%
“…For example, the bimodal profile implies that the MFR exists prior to eruption; see Figure 8 in [37] for more details. In addition, the elemental abundances are not uniform within one cross section either [39]. Therefore, a spacecraft can detect different composition profiles when it crosses one MC along the blue and black arrows as shown in Figure 1B, which are located in the same cross section perpendicular to the axis but with different impact factors.…”
Section: Introductionmentioning
confidence: 99%
“…The charge states within ICMEs are frozen-in near the Sun [33], and the relative abundances of elements with different first ionization potentials (FIPs) are different obviously in the corona and photosphere [34,35]. As the composition does not alter during CME propagation to 1 AU and beyond [36], the in situ data are also employed to analyze the MFR formation [28,37,38] and plasma origin [39,40] of CMEs. So far, the most complete composition data of ICMEs are provided by the solar wind ion composition spectrometer (SWICS) aboard Advanced Composition Explorer (ACE) and Ulysses, which can provide the charge states and elemental abundances of ∼10 elements [41].…”
Section: Introductionmentioning
confidence: 99%